Acceptance and Development of Beyond Banking Ecosystems - Voigt, Sebastian; Holland, Alexander (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
This paper aims to examine the acceptance and development of Beyond Banking Ecosystems. It analyzes current market trends, the phenomena and classifications these ecosystems exhibit, and how their acceptance among bank customers can be evaluated. Current market studies are first reviewed to validate the research questions of relevance and acceptance of Beyond Banking services, followed by expert interviews from banking sectors to gain deeper insights into existing activities and assess potential business models. Additionally, a survey is conducted to gauge customer interest and acceptance. The results of this paper form the basis for the future design of a scalable ecosystem beyond banking. Its development will provide bank decision-makers with knowledge and a practical tool for strategically aligning beyond-banking initiatives.